Amantadine-induced conformational and dynamical changes of the influenza M2 transmembrane proton channel - Cady, Sarah D. (National Academy of Sciences, 2008)
The M2 protein of influenza A virus forms a transmembrane proton channel important for viral infection and replication. Amantadine blocks this channel, thus inhibiting viral replication. Elucidating the high-resolution structure of the M2 protein and its change upon amantadine binding is crucial for designing antiviral drugs to combat the growing resistance of influenza A viruses against amantadine. We used magic-angle-spinning solid-state NMR to determine the conformation and dynamics of the transmembrane domain of the protein M2TMP in the apo- and amantadine-bound states in lipid bilayers. (13)C chemical shifts and torsion angles of the protein in 1,2-dilauroyl-sn-glycero-3-phosphatidylcholine (DLPC) bilayers indicate that M2TMP is α-helical in both states, but the average conformation differs subtly, especially at the G34–I35 linkage and V27 side chain. In the liquid-crystalline membrane, the complexed M2TMP shows dramatically narrower lines than the apo peptide. Analysis of the homogeneous and inhomogeneous line widths indicates that the apo-M2TMP undergoes significant microsecond-time scale motion, and amantadine binding alters the motional rates, causing line-narrowing. Amantadine also reduces the conformational heterogeneity of specific residues, including the G34/I35 pair and several side chains. Finally, amantadine causes the helical segment N-terminal to G34 to increase its tilt angle by 3°, and the G34–I35 torsion angles cause a kink of 5° in the amantadine-bound helix. These data indicate that amantadine affects the M2 proton channel mainly by changing the distribution and exchange rates among multiple low-energy conformations and only subtly alters the average conformation and orientation. Amantadine-resistant mutations thus may arise from binding-incompetent changes in the conformational equilibrium.